The efficacy of combination of oral antioxidants and topical retinoic acid versus topical retinoic acid monotherapy in mild acne vulgaris patients - Mawu, Ferra Olivia; Kapantow, Marlyn Grace; Christopher, Paulus Mario (Published by Universitas Gadjah Mada, 2025)
Acne vulgaris (AV) is a chronic inflammatory disorder of the pilosebaceous follicle with multifactorial pathogenesis and pleiomorphic clinical manifestations constituting comedones, papules, pustules, nodules, and cysts. Oxidative stress has been reported to contribute in AV pathogenesis. This phenomenon rationalizes antioxidant supplementation as an adjuvant therapy for AV management. Four cases of 22 to 23 yo women with complaints of worsening facial acne for 1 to 6 mo. Initially, acne lesions appeared as skin-colored papules, which increased in number, became reddish papules and pustules, and extended to the jaw and chin. Lesions were accompanied by temporary itching and pain. Dermatological examination revealed multiple circumscribed discrete erythematous papules, miliar to lenticular in size, comedones (+), and pustules (+), with total lesions <30. According to the Lehmann criteria, patients were diagnosed as mild AV. All patients were treated with 0.025% topical retinoic acid cream, while the other two patients received additional oral antioxidant supplementations (zinc and ɑ-lipoic acid) and were followed up every two weeks. Two cases who received additional oral antioxidant supplementations (Group A) exhibited an earlier and higher clinical improvement, characterized by a reduction in the number of lesions on each follow up, till the current report. Oxidative stress in AV pathogenesis causes microenvironment alteration that favours colonization of Cutibacterium acnes. Together with the increase in sebum production, it stimulates the release of pro-inflammatory cytokines, such as interleukin (IL)-1α, IL-8, and tumor necrosis factor-α (TNF α), contributing to the inflammatory response. Antioxidant supplementation plays a role in suppressing the process of lipid peroxidation and inhibiting the expression of pro-inflammatory cytokines. Comprehensive management of AV is based on pathogenesis and the role of oxidative stress. An earlier and higher clinical improvement reduction was noted in Group A, patients who received a combination of 0.025% topical retinoic acid cream and oral antioxidant supplementation.